Faunistic analyses and population fluctuation of fruit flies in a citric orchard in Dionisio Cerqueira, Santa Catarina, Brazil - Daniele Bertol de Lara; Flávio Roberto Mello Garcia (Biotemas, 2006)
With the objective of identifying the species of fruit flies and their fluctuation, and to characterize a citrus orchard in Dionísio Cerqueira in relation to the species of tephritids, this work of population dynamics was carried out in the period of September to August 2004. The survey was made using flytraps of the McPhail type with 10% inverted glucose. In the characterization of this orchard, the indices for abundance, constancy, dominance, frequency and diversity were calculated. The highest population level of Anastrepha fraterculus was in March and April. None of the analyzed climatic variables correlated with the captures of A. fraterculus and A. grandis. The collected females belonged to seven species and two genera. Anastrepha fraterculus was the most abundant, constant, frequent and dominant species, and was therefore considered as predominant. The index of diversity for the orchard was 1.09.